Le Saint-Laurent, facteur de localisation industrielle - Cazalis, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1967)
With almost 100 million tons of cargo yearly, of which more than 80 millions pass through Québec ports, the St. Lawrence is an important artery of transport. The fluvial communications System, comprising gulf, estuary, river, and the Great Lakes, extends deep into the north American continent; Duluth, for example, is 2,200 miles from the sea. Although the Seaway has opened the Great Lakes to ocean-going ships, the general increase in tonnage and draught of these vessels has allowed Québec ports, located at the break point between maritimes and Great Lakes traffic, to maintain their privileged position. Nevertheless, transhipment cargoes here are not particularly impressive (about 30 million tons yearly, mainly cereals) if one considers the enormous industrial capacity of the basin; this is because the Great Lakes-St. Lawrence network is in many ways an autonomous unit, essentially continental, and supplied from the interior rather than from the exterior, as is the case of the Rhine basin, for example. In Québec, cargoes originating from « secondary » industries scattered along the river and its tributaries (for example, the Saguenay) are relatively unimportant in terms of tonnage ... only 22 million tons of cargo from these industrial zones pass through Québec ports. Only 3.9% 0of the 6,539 factories located in cities touching on water, and only 13% of the total industrial payroll in these cities, are directly related to the St. Lawrence. This « underuse »of the river can be explained by Québec s industrial structure, geared to the production of consumer goods for local markets ; in contrast, Ontario has much heavy industry tied directly to the St. Lawrence network.